Pengaruh Pelatihan Preceptor Mentor terhadap Kepuasan Mahasiswa dalam Bimbingan Praktik Klinis - Nurul Aziza Ath Thaariq; Mahdalena Prihatin Ningsih; Lisa Rahmawati (Poltekkes Kemenkes Padang, 2024)
Clinical practice learning is a learning activity held in practice settings such as hospitals, clinics, health centers and communities. Phenomenological studies state that the duties and responsibilities as a preceptor cannot be carried out optimally. Surveying student perceptions regarding the role of preceptors in practice areas, 12% stated that preceptors were less cooperative, less friendly, and less guiding; 11.3% stated that preceptors were busy with other tasks, and 15.3% stated that preceptors were busy with patients. The aim of the research was to determine the effect of preceptor mentor training on student satisfaction at the Padang DII Midwifery Study Program, Padang Ministry of Health Polytechnic. This research is quantitative research with a cross-sectional approach. The research population was clinical practice supervisors in hospitals, community health centers, and midwives' independent practice in West Sumatra. The sampling technique used total sampling with a total of 80 respondents. The research instrument is a questionnaire. The research results showed that out of a total of 80 respondents, 47 respondents (58.75%) had participated in preceptor mentor training and 38.75% of them had received student satisfaction ratings in the high category in guiding students. Conclusion : The Chi-square test result is 0.000, preceptor mentor training has an influence on student satisfaction at the DIII Midwifery Study Program, Padang Health Polytechnic, Ministry of Health, Padang in guiding clinical practice in the practice area. Recommended that the institution to collaborate with the hospital so that preceptorship training can be carried out jointly and complement each other between clinical and academic supervisors.